"FIVE YEAR STUDY OF ELDERLY PRIMIGRAVIDA AT AMIN HOSPITAL ISFAHAN UNIVESITY" - M. Moshir-Fatemi; M. Ahmadi; M.A. Sajjad; M. Azari Dorcheh (Tehran University of Medical Sciences, 1977)
Pregnancy, labor and delivery are known to be associated with higher rate of fetal and neonatal complications in old primigravidas. In a period of 5 rears (2531 - 36) there were 30000 deliveries at Amin hospital, among them, there are records of 355 deliveries in primigravidas over 35 years of age who are included in this retrospective study. Comparison with the same number of primigravidas under 30 years of age (a random selection, control group) indicate a much higher rate of fetal and neonate mortality as well as other minor and major complications id older group. Incidence of breech presentation and twins was high, duration of pregnancy, first and second stage of labor also was longer, but the third state was not significantly different from control group. Spontaneous delivery occurred in fewer cases, instead operative deliveries including forceps and vacuum deliveries were more frequent and the rate of cesarean-section was high (19.4% comparing with 5.5% in control group). Toxemia of pregnancy, hyper tension, ante partum and postpartum, hemorrhage, fetal and neonatal mortality showed an increased' frequency in the studied group butt distribution of congenital malformations were found to be equal except that a case of Down syndrome was recorded in the studied group.